What Drives Racial and Ethnic Differences in High-Cost Mortgages? The Role of High-Risk Lenders - Bayer, Patrick; Ferreira, Fernando; Ross, Stephen L. (Review of Financial Studies, 2018)
This paper examines racial and ethnic differences in high-cost mortgage lending in seven diverse metropolitan areas from 2004 to 2007. Controlling for credit score and other risk factors, African American and Hispanic borrowers are 103% and 78% more likely to receive high-cost mortgages for home purchases. A large part of the increase is attributable to sorting across lenders (55%-65%), and this, in turn, can be largely accounted for by the lender’s ex post foreclosure risk. The remaining within-lender differences are also concentrated in high-risk lenders, revealing the central role of these institutions in explaining market-wide racial and ethnic differences. Received December, 17 2014; editorial decision January 20, 2017 by Editor Philip Strahan.